Citizenship in Iraq after 2003... A study of the causes and challenges - Ajeel, Emad Wakaa (Tikrit Journal For Political Science, 2023)
Citizenship, with a simple definition, is represented by the rights and duties guaranteed by the constitution, and among these rights is the right to political, social, economic, media and cultural participation, in addition to equality before the law. Preferring the national interest over the local interest. The citizenship crisis is an important factor in achieving political and social development, because the efforts that can be made to overcome the crisis aim at forming and strengthening the political and social structure. The pluralism that Iraqi society enjoys is not a negative condition, but rather there are those He tried to use this social fabric for the purpose of achieving political or social gains by provoking sectarian strife, killing over identity, displacement, and other methods that the Iraqi people realized are dangerous, so it requires the political system in Iraq to believe in pluralism in all fields in order to preserve the rights and freedoms of all An individual, which in turn forms the basis for building citizenship.